Functional connectivity of paired default mode network subregions in primary insomnia - Nie X; Shao Y; Liu SY; Li HJ; Wan AL; Nie S; Peng DC; Dai XJ (Neuropsychiatric Disease and Treatment, 2015)
Xiao Nie,1,* Yi Shao,2,* Si-yu Liu,3 Hai-jun Li,1 Ai-lan Wan,4 Si Nie,1 De-chang Peng,1 Xi-jian Dai1,5 1Department of Radiology, The First Affiliated Hospital of Nanchang University, Nangchang, Jiangxi, People’s Republic of China; 2Department of Ophthalmology,The First Affiliated Hospital of Nanchang University, Nangchang, Jiangxi, People’s Republic of China; 3Medical College of Nanchang University, Nangchang, Jiangxi, People’s Republic of China; 4Department of Psychosomatic Medicine, The First Affiliated Hospital of Nanchang University, Nangchang, Jiangxi, People’s Republic of China; 5Brain Cognition and Brain Disease Institute, Shenzhen Institutes of Advanced Technology, Chinese Academy of Sciences, Shenzhen, People’s Republic of China *These authors contributed equally to this work Objective: The aim of this study is to explore the resting-state functional connectivity (FC) differences between the paired default mode network (DMN) subregions in patients with primary insomnia (PIs).Methods: Forty-two PIs and forty-two age- and sex-matched good sleepers (GSs) were recruited. All subjects underwent the resting-state functional magnetic resonance imaging scans. The seed-based region-to-region FC method was used to evaluate the abnormal connectivity within the DMN subregions between the PIs and the GSs. Pearson correlation analysis was used to investigate the relationships between the abnormal FC strength within the paired DMN subregions and the clinical features in PIs.Results: Compared with the GSs, the PIs showed higher Pittsburgh Sleep Quality Index score, Hamilton Anxiety Rating Scale score, Hamilton Depression Rating Scale score, Self-Rating Depression Scale score, Self Rating Anxiety Scale score, Self-Rating Scale of Sleep score, and Profile of Mood States score (P<0.001). Compared with the GSs, the PIs showed significant decreased region-to-region FC between the medial prefrontal cortex and the right medial temporal lobe (t=-2.275, P=0.026), and between the left medial temporal lobe and the left inferior parietal cortices (t=-3.32, P=0.001). The abnormal FC strengths between the DMN subregions did not correlate with the clinical features.Conclusion: PIs showed disrupted FC within the DMN subregions. Keywords: insomnia, functional connectivity, default mode network, functional magnetic resonance imaging, resting-state, blood oxygenation level dependent